The Relationship between Spiritual Health and Public Health Aspects among Patients with Breast Cancer - Mohammad Moradi-Joo; Towhid Babazadeh; Zeynab Honarvar; Sahar Mohabat-Bahar; Fatemeh Rahmati-Najarkolaei; Morteza Haghighi (پژوهش در دین و سلامت, 2017)
For downloading the full-text of this article please click here.